KONSEP KEPEMIMPINAN DALAM ISLAM: KARAKTERISTIK KEPEMIMPINAN PROFETIK UMAR BIN KHATTAB - Amni, Nuri; Nida, Sautun; Rahmat, Uswatun Hasanah (Department of Islamic Education Management, 2025)
Leadership in the context of Islam offers a unique framework, especially through the prism of prophetic leadership. One of the main examples is Umar bin Khattab, a friend and leader known for his just and firm leadership. This study aims to explore the concept of Umar bin Khattab's leadership and its implications in the contemporary context. The purpose of this study is to explore the concept of prophetic Islamic leadership as illustrated through the example of Umar bin Khattab. The focus is to analyze the main values, principles, and practices of leadership applied by Umar bin Khattab and their impact on society at that time. This study uses a qualitative approach with a library research approach. The data sources in this study are scientific books, research reports, scientific papers, and journals, especially the sirah (biography) of Umar bin Khattab, hadith, and Islamic literature. Data were collected and analyzed to identify leadership patterns applied by Umar bin Khattab. Umar bin Khattab was found to implement leadership based on justice, active community participation, and personal example. The impact is seen in the decision-making process. These principles provide inspiration for contemporary leaders in understanding and implementing the concept of prophetic Islamic leadership. This study provides in-depth insight into the concept of leadership in prophetic Islam through a case study of Umar bin Khattab, and emphasizes its relevance in the modern context.